2011
DOI: 10.1179/102453311x13127324303353
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of FAS receptor/FAS ligand and TrailR1/TrailR2 in acute myeloid leukemia

Abstract: We studied the expressions of FR, FL, TR1, and TR2 on blasts and T cells from 71 patients with acute myeloid leukemia (AML) and correlated expression rates with the clinical course. Compared to AML-blasts we found higher co-expressions on healthy myeloid and T cells. Expression of all markers on blasts and on T cells was similar in different subtypes and acute stages of AML. Compared to the non-responders (n = 7) responders to the AML Cooperative Group-therapy (n = 22) presented with higher proportions of blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Lower expression of these molecules, which are involved in the commencement of the apoptotic pathway, aids cancerous cells in avoiding apoptosis. In line with our results, Prodzik et al, using flowcytometry, reported a significantly lower expression of FAS and DR4 in AML patients compared to controls ( 3 ). As the mentioned study evaluated the protein expression, it also confirms that gene expression levels of FAS and DR4 show a good correlation with the protein expression levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lower expression of these molecules, which are involved in the commencement of the apoptotic pathway, aids cancerous cells in avoiding apoptosis. In line with our results, Prodzik et al, using flowcytometry, reported a significantly lower expression of FAS and DR4 in AML patients compared to controls ( 3 ). As the mentioned study evaluated the protein expression, it also confirms that gene expression levels of FAS and DR4 show a good correlation with the protein expression levels.…”
Section: Discussionsupporting
confidence: 93%
“…A better understanding of the genetic and molecular basis of AML may lead to improve treatment outcomes for patients. Evasion of programmed cell death (apoptosis) is a key step in cancer pathogenesis ( 3 ). There are 2 main apoptotic pathways: extrinsic and intrinsic.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, most immunohistochemical studies performed so far to evaluate TRAIL receptor expression in primary tumour tissues are poorly informative due to a lack of specific evaluation of membrane‐bound expression levels of these receptors. Nonetheless, heterogeneous expression levels of TRAIL receptors have been found in a large variety of tumours (Strater et al ., ; Min et al ., ; McCarthy et al ., ; van Geelen et al ., ; Kuijlen et al ., ; Cooper et al ., ; Granci et al ., ; Ganten et al ., ; Leithner et al ., ; Macher‐Goeppinger et al ., ; Pordzik et al ., ). However, their expression level is probably overestimated by the fact that most of these studies revealed mainly cytoplasmic expression.…”
Section: Study Design and Administration Of Trail And Derivatives: Lementioning
confidence: 99%
“…The out of control regulation of apoptosis could make a contribution to the pathogenesis of malignancies, such as ovarian cancer, breast cancer and neuroblastoma ( 5 7 ). Among haematological cancers, Fas-mediated apoptosis was presented in multiple myeloma, Burkitt's lymphoma and acute myeloid leukemia (AML) ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%